Modulation of motor evoked potentials by muscle vibration: The role of vibration frequency - Siggelkow, Sabine; Kossev, Andon; Schubert, Margot; Kappels, Hans-Hermann; Wolf, Werner; Dengler, Reinhard (Muscle & nerve, 1999)
Augmentation of motor evoked potentials (MEPs) by muscle vibration (MV) was studied in 10 healthy subjects with regard to the vibration frequency (VF). The extensor carpi radialis muscle (ECR) was vibrated using VFs of 80, 120, and 160 Hz. Motor evoked potentials following transcranial magnetic stimulation were recorded simultaneously from the vibrated ECR and the antagonist flexor carpi radialis muscle (FCR) without MV, 0.5 s and 3 s after onset of MV and 1 s after offset. Only the VFs of 80 Hz and 120 Hz caused MEP augmentation and latency shortening in ECR, whereas depression of MEPs in FCR was induced by all VFs used. It appears that MEP augmentation and latency shortening in ECR are mediated by the primary muscle spindle endings which respond with optimal discharge rates to VFs of up to 100 Hz. Motor evoked potential depression in FCR, being well expressed also with VF 160 Hz, seems to involve other dynamic mechanoreceptors. © 1999 John Wiley & Sons, Inc. Muscle Nerve 22: 1544–1548, 1999